The Role of Alterations in Alpha-Klotho and FGF-23 in Kidney Transplantation and Kidney Donation - Gupta, Meera; Orozco, Gabriel; Rao, Madhumati; Gedaly, Roberto; Malluche, Hartmut H.; Neyra, Javier A. (Frontiers in Medicine, 2022)
Cardiovascular disease and mineral bone disorder are major contributors to morbidity and mortality among patients with chronic kidney disease, and often persist after renal transplantation. Ongoing hormonal imbalances after kidney transplant (KT) are associated with loss of graft function and poor outcomes. Fibroblast growth factor 23 (FGF-23) and its co-receptor, α-Klotho, are key factors in the underlying mechanisms that integrate accelerated atherosclerosis, vascular calcification, mineral disorders, and osteodystrophy. On the other hand, kidney donation is also associated with endocrine and metabolic adaptations that include transient increases in circulating FGF-23 and decreases in α-Klotho levels. However, the long-term impact of these alterations and their clinical relevance have not yet been determined. This manuscript aims to review and summarize current data on the role of FGF-23 and α-Klotho in the endocrine response to KT and living kidney donation, and importantly, underscore specific areas of research that may enhance diagnostics and therapeutics in the growing population of KT recipients and kidney donors.